APPLICATION OF SYSTEMATIC DESENSITIZATION COGNITIVE BEHAVIOR THERAPY TO REDUCE NEGATIVE PERCEPTIONS OF STUDENTS TOWARDS TEACHERS - Holisah Holisah; Andi Wahyu Irawan (LP2M IAI Al-Khairat Pamekasan, 2026)
Students’ negative perceptions of teachers are emotional responses arising from learning experiences that are perceived as authoritarian, unpleasant, or unfair. Such conditions may hinder the learning process, reduce motivation, and decrease academic engagement. One intervention commonly employed is Systematic Desensitization, a component of Cognitive Behavior Therapy (CBT), which is a psychological technique that trains students to face anxiety-provoking stimuli gradually while practicing relaxation. The research involved 48 tenth-grade students at SMK Negeri 6 Samarinda, randomly selected from a population of 80 students and assigned to an experimental group (Class X Heavy Equipment Engineering 1) and a control group (Class X Mechanical Engineering 1). The study utilized a true experimental method with a pretest–posttest control group design. The instrument used was a Likert-scale questionnaire adapted from the Teacher–Student Relationship Questionnaire (TSRQ), with a reliability coefficient of α = 0.970. Independent Sample T-Test analysis revealed a significant reduction in negative perceptions among the experimental group after six intervention sessions, whereas the control group did not show any meaningful change.